AB0723 Seroprevalence of epstein-barr virus and cytomegalovirus in systemic sclerosis patients: preliminary results. (12th June 2018) - Trombetta, A.C.; Tomatis, V.; Alessandri, E.; Paolino, S.; Pizzorni, C.; Ghio, M.; Ruaro, B.; Patane, M.; Gotelli, E.; Goegan, F.; Sulli, A.; Smith, V.; et al.
Abstract : Background: Epstein-Barr Virus (EBV) and cytomegalovirus (CMV) are among the most diffused virus in humans, with prevalence of 90% and 80% respectively in adult immunocompetent population 1, 2 . Hypothesis for a role of EBV and CMV in systemic sclerosis pathogenesis was reported 3 . Objectives: To evaluate the prevalence of EBV and CMV in a population of patients affected by SSc. As an exploratory aim, correlations with available clinical variables were evaluated. Methods: A total of 49 patients (44 females and 5 males, age 65, 6±9 years, 34 with limited cutaneous involvement and 14 with diffused cutaneous involvement) diagnosed according to the 2013 ACR/EULAR criteria 4 were randomly enrolled at their follow-up visit for a further more detailed analysis. After consent, all participants undergone serological testing for VCA-IgM, VCA-IgG and EBNA-IgG and CMV IgM and IgG, to determine prior or actual EBV and/or CMV infection. All SSc patients undergone also to clinical examination and instrumental evaluations according to SSc clinical standard follow up. Results: Results for EBV seroprevalence were: VCA-IgM negative=43 (87%), positive=4 (8, 2%), borderline=2 (4, 1%) in all SSc patients. VCA-IgG resulted positive in 48 patients (98%) and EBNA-IgG resulted positive in 40 (81, 6%) patients, borderline in 4 (8, 2%) and negative in 5 (10, 2%) patients. Forty-six (93, 9%) patients resulted positive for CMV-IgG and 22 (44, 9%) showed detectable CMV IgM. Consequently, EBV and CMV seroprevalence was significantly higher (p=0.01 and p=0.032 respectively) than that calculated in general population (90% and 80% respectively). Interestingly, the presence of higher CMV-IgM correlated linearly with higher pulmonary arterial pressure values (p=0.036) and was different in patients with or without sicca syndrome (p=0.012) and arthralgias (p=0.04). Finally, higher CMV-IgG correlated with diffused cutaneous SSc form (p=0.023) and nephropathy (p=0.036). Conclusions: The seroprevalence of EBV and CMV positivity was found significantly higher in the sample of SSc patients. EBV seropositivity (VCA-IgG) was present nearly in the totality of patients (98%). Of relevance, the high presence of CMV-IgG (93%) and CMV-IgM (44.9%) in SSc patients: the last correlated linearly with higher pulmonary arterial pressure values. EBV and CMV infections, among the supposed triggers in several autoimmune diseases, might also play a role in SSc patients, at least with progressive disease. References: [1] Rickinson AB, et al. Fields virology. Philadelphia: Lippincott Williams and Wilkins; 2001. pp. 2575–2627 [2] Kano Y1, et al. Dermatol Sci. 2000;22:196–204 [3] Arnson Y, et al. Ann N Y Acad Sci. 2009Sep;1173:627–32. [4] van den Hoogen F, et al. Ann Rheum Dis. 2013;72:1747–1755. Disclosure of Interest: None declared